2006
DOI: 10.1128/jb.188.7.2666-2673.2006
|View full text |Cite
|
Sign up to set email alerts
|

Genes and Enzymes Involved in Caffeic Acid Biosynthesis in the Actinomycete Saccharothrix espanaensis

Abstract: The saccharomicins A and B, produced by the actinomycete Saccharothrix espanaensis, are oligosaccharide antibiotics. They consist of 17 monosaccharide units and the unique aglycon N-(m,p-dihydroxycinnamoyl)taurine. To investigate candidate genes responsible for the formation of trans-m,p-dihydroxycinnamic acid (caffeic acid) as part of the saccharomicin aglycon, gene expression experiments were carried out in Streptomyces fradiae XKS. It is shown that the biosynthetic pathway for trans-caffeic acid proceeds fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
119
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(125 citation statements)
references
References 33 publications
5
119
0
1
Order By: Relevance
“…Our present findings stimulated us to re-examine the genome sequence of S. coelicolor [24]. Blast search revealed one gene with 32% identity to the tyrosine ammonia-lyase Sam8 of Saccharothrix espanaensis [21]. This gene, SCO4932, is currently annotated as histidine ammonia-lyase.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Our present findings stimulated us to re-examine the genome sequence of S. coelicolor [24]. Blast search revealed one gene with 32% identity to the tyrosine ammonia-lyase Sam8 of Saccharothrix espanaensis [21]. This gene, SCO4932, is currently annotated as histidine ammonia-lyase.…”
Section: Discussionmentioning
confidence: 78%
“…In Actinomycetes, however, these compounds are relatively rare, and only recently it was demonstrated that several Actinomycetes possess phenylalanine ammonialyase (PAL) and tyrosine ammonia-lyase (TAL) genes for the biosynthesis of cinnamic and coumaric acid [21,22]. However, neither in the biosynthetic gene cluster of clorobiocin, nor in the completely sequenced genome of S. coelicolor, PAL or TAL genes have been described so far.…”
Section: Discussionmentioning
confidence: 99%
“…In the last years, several studies have used the enzymes involved in the phenylpropanoid pathway to produce compounds other than curcuminoids, such as phenylpropanoic acids (coumaric acid, caffeic acid, and ferulic acid) (140,141,151,152,(154)(155)(156)(157), stilbenoids (155,158), and flavonoids (116,117,150,155,(159)(160)(161)(162). In the design and construction of those pathways, some enzymes from other organisms were used that could also be considered for the optimization of the heterologous production of curcuminoids.…”
Section: Figmentioning
confidence: 99%
“…Berner et al (154) studied the caffeic acid biosynthetic pathway in the actinomycete Saccharothrix espanaensis and heterologously expressed it in Streptomyces fradiae XKS, a polyketide synthase-defective mutant strain that is considered to be a very convenient host for expression experiments (166). Streptomyces, applied in the production of a wide range of secondary metabolites, including polyketides, can be another candidate for the heterologous production of plantspecific polyketides (167).…”
Section: Figmentioning
confidence: 99%
“…[22] Hence a depigmenting enzyme - [7] and Saccharothrixespanaensis (Gen-Bank accession number: ABC88669). [8] This variety reflects the enzyme's specialized role in p-coumaric acid biosynthesis.Tyrosine ammonia-lyase (TAL, EC 4.3.1.5) has recently been described as a member of the aromatic amino acid lyase family of enzymes, which also includes phenylalanine ammonia-lyase (PAL, EC 4.3.1.5) and histidine ammonia-lyase (HAL, EC 4.3.1.3). [4] TAL is required for deamination of the amino acid L-tyrosine to p-coumaric acid and releases ammonia.…”
Section: Introductionmentioning
confidence: 99%